2021
DOI: 10.1631/jzus.b2000802
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of Bcl-2 regulation of cell cycle arrest: insight into the mechanisms

Abstract: B cell lymphoma 2 (Bcl-2) is an important antiapoptotic gene that plays a dual role in the maintenance of the dynamic balance between the survival and death of cancer cells. In our previous study, Bcl-2 was shown to delay the G0/G1 to S phase entry by regulating the mitochondrial metabolic pathways to produce lower levels of adenosine triphosphate (ATP) and reactive oxygen species (ROS). However, the detailed molecular mechanisms or pathways by which Bcl-2 regulates the cell cycle remain unknown. Here, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…Our present findings showed that CR inhibit the pro-apoptotic proteins BAX, pJNK and Caspase 3 by enhancing BCL-2 expression. However, this last result is also in according with evidence from the literature that highlight a non-apoptotic role of Bcl-2 related to an inhibitory effect on the cell cycle depending on a cyclin/cyclin-dependent kinase (CDK) inhibitor p27 [70][71][72]. In agreement with these observations our results showed that Bcl-2 overexpression in OA vs Y group, results in elevated levels of p27 protein.…”
Section: Discussionsupporting
confidence: 92%
“…Our present findings showed that CR inhibit the pro-apoptotic proteins BAX, pJNK and Caspase 3 by enhancing BCL-2 expression. However, this last result is also in according with evidence from the literature that highlight a non-apoptotic role of Bcl-2 related to an inhibitory effect on the cell cycle depending on a cyclin/cyclin-dependent kinase (CDK) inhibitor p27 [70][71][72]. In agreement with these observations our results showed that Bcl-2 overexpression in OA vs Y group, results in elevated levels of p27 protein.…”
Section: Discussionsupporting
confidence: 92%
“…The results of KEGG analysis revealed that this protein possessed Poxvirus-BCL-2-like motifs, thus, it might be involved in immunomodulation of apoptosis in host cells. The infected cells embody the apoptotic cell death to evade the spread of viruses to the neighboring cells [ 40 ]. To avoid this evasion, the viral BCL-2 protein regulates this activity in the individual host, accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, caspase‐9 cleaves and activates the effector caspases‐3 to bring about apoptosis (Araya et al, 2021). Bcl‐2 is an important anti‐apoptotic biomarker that plays a dual role in maintaining the dynamic balance between cell survival and death (Du et al, 2021; Mazel et al, 1996). Bax is a gene that regulates the apoptotic pathway, and we report an increased Bax/Bcl‐2 ratio following BbF treatment, suggesting that apoptosis is favored in BEAS‐2B and 16HBE cells (Shi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%